2020
DOI: 10.1007/s10064-020-01948-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of climate change induced extreme precipitation on landslide activity in the Three Gorges Reservoir, China

Abstract: Climate change has caused an increase in extreme rainfall and snowfall in many parts of the world. For example, in the Three Gorges Reservoir area, annual precipitation has gradually increased and the occurrence of heavy precipitation events has become more frequent. As the reservoir water level rises in October, the high water combined with heavy precipitation creates a "special hydrological environment," which recently caused the Yanguan landslide. The Yanguan landslide is a large-scale soil landslide that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…An escalation in the occurrence of extreme rainfall events in alpine regions can intensify the occurrence of landslides (Shah et al, 2023). Beyond the direct erosive impact of rainfall, extreme precipitation can also induce landslides by influencing the hydrology of the watershed (Zhu et al, 2021). Most landslides in this part of the plateau are triggered by rainfall (Li et al, 2023;Peng et al, 2015).…”
Section: What Is the Relationship Between Landslide Deformation And P...mentioning
confidence: 99%
“…An escalation in the occurrence of extreme rainfall events in alpine regions can intensify the occurrence of landslides (Shah et al, 2023). Beyond the direct erosive impact of rainfall, extreme precipitation can also induce landslides by influencing the hydrology of the watershed (Zhu et al, 2021). Most landslides in this part of the plateau are triggered by rainfall (Li et al, 2023;Peng et al, 2015).…”
Section: What Is the Relationship Between Landslide Deformation And P...mentioning
confidence: 99%
“…In China, many large-scale landslides were triggered by heavy rainfall, such as the Yigong landslide [10], rockslide debris in the Wenchuan earthquake area [11], and Yanguang and Shaziba landslide in Hubei [12,13]. However, shallow landslides (generally lower than 2 m) are the primary and common phenomena worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…While the impact of extreme weather on infrastructure is more pronounced, changes in average climate conditions also significantly affect geotechnical infrastructure. Zhu et al (2021) studied the effect of climate change-induced heavy rainfall events on landslides in China and found that the factor of safety significantly drops under future climate. The gravity of soil erosion in Iran is set to change under the predicted rainfall patterns (Doulabian et al 2021).…”
Section: Introductionmentioning
confidence: 99%